Rethinking Public Pension Reform Initiatives - Heller, Peter (IMF Working Papers; Working Paper ;, 1998)
This paper argues that there are significant risks, limitations, and complications associated with reliance upon mandatory DC, fully funded schemes as the dominant public pension pillar. Policies to limit risks may result in the government being reinjected into playing an important financial role in the provision of social insurance. For many countries, the principal source of old age support should thus derive from a well-formulated, public DB pillar, with a significant amount of prefunding. A DC/FF pillar can play a useful supplemental role in a multi-pillar system for the accumulation of pension savings.